Dark Traces of the Past : Psychoanalysis and Historical Thinking. - Straub, Jürgen (Berghahn Books, 2011)
The relationship between historical studies and psychoanalysis remains an open debate that is full of tension, in both a positive and a negative sense. In particular, the following question has not been answered satisfactorily: what distinguishes a psychoanalytically oriented study of historical realities from a historical psychoanalysis? Skepticism and fear of collaboration dominate on both sides. Initiating a productive dialogue between historical studies and psychoanalysis seems to be plagued by ignorance and, at times, a sense of helplessness. Interdisciplinary collaborations are rare. Emp.